Analytic Solution for the RL Electric Circuit Model in Fractional Order. (16th June 2014) - Shah, P. V.; Patel, A. D.; Salehbhai, I. A.; Shukla, A. K.
Abstract : This paper provides an analytic solution of R L electrical circuit described by a fractional differential equation of the order 0 < α ≤ 1 . We use the Laplace transform of the fractional derivative in the Caputo sense. Some special cases for the different source terms have also been discussed.